Overlapping Authority of Notaries and Land Deed Officials in Making Power of Attorney to Impose the Mortgage Rights - Fonnyta Laurenzia Rosiga; Bayu Indra Permana (Universitas Islam Darul Ulum, 2025)
This study aims to examine the imbalances that occur in the implementation of these authorities and evaluate whether the regulations and implementation are in line with the principle of legal certainty. Problems arise when this overlapping authority causes a gap between das sein and das sollen. The granting of authority to Notaries and Land Deed Officials in making Power of Attorney to Impose the Mortgage Rights is a dual authority that opens up room for debate regarding the clarity of the boundaries and legitimacy of each party in making Power of Attorney to Impose the Mortgage Rights, especially in relation to the making of land deeds. This study uses a normative legal approach, namely an approach that focuses on the study of positive legal norms. The results of the discussion are that Power of Attorney to Impose the Mortgage Rights made before Notaries using the format according to letter H (Attachment 23) of Article 96 paragraph (1) of Perkaban Number 8 of 2012 do not meet the requirements as authentic deeds and are contrary to Article 1868 of the Civil Code, Article 1 Number (7) and Article 38 Notary Law. Legal disharmony related to the norms governing Power of Attorney to Impose the Mortgage Rights is a vertical disharmony because it concerns the conflict between statutory regulations with different hierarchies that regulate the same thing, namely between Perkaban Number 8 of 2012 and Notary Law. Legal harmonization must be the heart of legal science in resolving the problem of disharmony between norms governing Power of Attorney to Impose the Mortgage Rights if this is not done then the Power of Attorney to Impose the Mortgage Rights deed made before a Notary will remain a problem all the time and cause chaos at the practical level.